Malaysian building information modelling (BIM) implementation roadmap: identifying stakeholders interest - Nor Aini , Abdul (2014)
Building Information Modelling (BIM) is an approach in which utilise a 3D parametric modelling as a primary technology. The approach brings many advantages and has attracted many players in Malaysian Construction industry and has led the industry to develop a roadmap to strategize the implementation. The roadmap is important to coordinate many activities amongst the industry groups working with adopters of BIM in Malaysia. The aim of the study is to support the development of BIM national roadmap by providing the data of the stakeholders' Interest of BIM implementation at the industrial level. Research methodology used in this research is qualitative in nature by engaging a workshop. The workshop was organised by Construction Industry Development Board (CIDB) Malaysia. In the workshop, six groups of stakeholders were formed to provide data and information regarding to the stakeholders' interest for BIM implementation. The stakeholders were academics, vendor & BIM consultant, facilities management, contractor & quantity surveyor, design consultant and public agency. Result from the workshop shows that the stakeholders interest basically tied to the three main objectives of construction delivery which are the quality, cost and time. Combining all the interests, 47 factors of interests were identified with some of them are overlapped between one stakeholders to another. Based on the occurrence that takes place during the discussion, the most discussed factors are the accuracy of BIM data, reduction of delivery time and improve understanding of the project information.